‘Not my dream’: Mother’s challenge of raising intellectual disability child in Vhembe district - Ndidzulafhi S. Raliphaswa; Mary Maluleke; Mutshinyalo L. Netshikweta (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2022)
Background: The birth of a child with an intellectual disability in a family brings confusion, depression and frustrations, especially to the mother. Activities required by these children place a heavy burden on mothers in terms of support and care, as most mothers are the ones who take full care in the well-being of a child, regardless of whether a child has an intellectual disability or not. Challenges include feeding, bathing, dressing, finance and assisting with elimination, especially when the child is a teenager, where one expects the child to be able to do everything for himself or herself.